Bacterial contamination in the different parts of household air conditioners: a comprehensive evaluation from Chengdu, Southwest China - Sun, Donglei; Tang, Li; Long, Keyan; Sun, Weilian; Zhang, Zunzhen (Frontiers in Public Health, 2024)
Air flow driven by air-conditioner has a significant impact on the indoor environment, however, the bacterial contamination conditions in the different parts of air-conditioners have not been fully elucidated. In this study, we assessed the bacterial pollution in the four parts, including air outlet, filter net, cooling fin and water sink, of ten household air-conditioners quantitatively and qualitatively from Chengdu, southwestern China. The microbial cultivation results showed the large total bacterial counts of 5042.0, 9127.6, 6595.1 and 12296.2 CFU/cm 2 in air outlet, filter net, cooling fin and water sink. Furthermore, the sequencing data showed that these four parts displayed different bacterial characteristics. At the level of genus, Caproiciproducens and Acidipropionibacterium were predominant in air outlet. Bacillus, Acinetobacter, Paracoccus and Corynebacterium were detected as the characteristic bacteria in filter net. For cooling fin, Rhodococcus, Achromobacter and Nocardioides were the dominant bacteria. The genera of Methylobacterium-Methylorubrum, Brevibacterium, Stenotrophomonas and Psychrobacter were identified as the bioindicators in water sink. The bioinformatic analysis on the sequencing data illustrated that the bacteria from air-conditioners were associated with metabolic disturbance. This study reveals the distinct bacterial compositions in the different parts of air-conditioner, and provides new clues for the non-negligible bacterial pollution in this common appliance from Chinese households.